POTENSI TANAMAN PANDAN LAUT (Pandanus tectorius) DAN LIMBAH INDUSTRI GANDUM KOTA CILEGON SEBAGAI BAHAN BAKU SINTESIS BIOETANOL - Agus Malik Ibrahim; Agrin Febrian Pradana; Gagas Priyosakti; Miftahul Arifin; Tuti Alawiyah; Perliansyah (BRIN Publishing, 2020)
The minimum requirement of bioethanol utilization (E100) as a mixture of fuel oil is required as much as 20%,of the total needs in January 2025 as stated in the Regulation of the Minister of Energy and Mineral Resourcesnumber 12 in 2015. Indonesia is a country that has many potential raw materials for the development of bioethanolas renewable energy, such as sea pandanus plants (Pandanus tectorius) and food industry wastes such as thewheat industry. Sea pandanus plants are commonly found throughout the Indonesian archipelago and are availableendemically. While wheat industrial waste is available in industrial areas such as in Banten Province, which has so farnot been utilized as a source of biofuels. The purpose of this research is to get bioethanol product from new sources basedon natural materials and industrial waste. The stages of research began with raw materials preparation, proximateanalysis, gelatinization, liquefaction, pre-saccharification, fermentation, distillation process, and quantitative analysisusing instruments. The results showed that the sea pandanus leaf had the potential for bioethanol synthesis with thehighest amount of recovery and efficiency were 309 mL and 0.62 mL/g respectively, whereas based on the results ofgas chromatography (GC) analysis, the bioethanol product which had the highest purity was from wheat bran waste witha purity level of 97.64%.